2017
DOI: 10.1189/jlb.3ma0217-054rr
|View full text |Cite
|
Sign up to set email alerts
|

Role of MyD88 signaling in the imiquimod-induced mouse model of psoriasis: focus on innate myeloid cells

Abstract: Psoriasis is a chronic skin disease associated with deregulated activation of immune cells and keratinocytes. In this study, we used the imiquimod (IMQ)-induced mouse model of psoriasis to dissect better the contribution of hematopoietic and skin-resident stromal cells to psoriasis development. The comparison of disease development in mice carrying the hematopoietic cell-specific deletion of MyD88 ( mice) with mice carrying the total MyD88 deficiency ( mice), we show that the progression of skin and systemic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
3
18
0
Order By: Relevance
“…Psoriasis macrophages secreted significantly more IL-23 following IL-36γ stimulation than healthy macrophages. Our findings also complement findings from an imiquimod-induced mouse model of psoriasis which has shown to be dependent on MyD88 signalling in macrophages ( 57 ). Whilst macrophage derived IL-23 is thought to be crucial to the immunopathological development of psoriasis lesions, we are the first to report a viable cytokine agonist for this induction, in IL-36γ.…”
Section: Discussionsupporting
confidence: 87%
“…Psoriasis macrophages secreted significantly more IL-23 following IL-36γ stimulation than healthy macrophages. Our findings also complement findings from an imiquimod-induced mouse model of psoriasis which has shown to be dependent on MyD88 signalling in macrophages ( 57 ). Whilst macrophage derived IL-23 is thought to be crucial to the immunopathological development of psoriasis lesions, we are the first to report a viable cytokine agonist for this induction, in IL-36γ.…”
Section: Discussionsupporting
confidence: 87%
“…This discrepancy can be explained considering that we use a full-length IL-38, whereas IL-36Ra was employed in a more active, N-terminally cleaved, form 7 , 43 . As two N-terminally cleaved forms of IL-38 with an increased inhibitory activity have been identified in tumor cells 44 , we hypothesize that IL-38 is processed in our in vivo experimental system, likely owing to extracellular neutrophil proteases abundantly released in the IMQ-treated skin 31 , 45 , 46 . Finally, the absence of a dose–response effect of IL-38 (as well as of IL-36Ra) on in vitro expression of inflammatory mediators support the hypothesis of Dinarello et al that IL-38 and IL-36Ra do not behave as classic receptor antagonists 5 .…”
Section: Discussionmentioning
confidence: 93%
“…Using a mouse model where the psoriatic phenotype is induced by topical application of the immunomodulator imiquimod, Costa et al demonstrated that induction of the phenotype depends exclusively on hematopoietic cells. Using conditional knockout mouse strains, the active contribution of monocytes and macrophages on disease propagation and exacerbation was shown ( 86 ). With regard to atherosclerosis, Tabas and Lichtman recently reviewed how macrophages can be programmed for functions on a spectrum from inflammatory and host defense to resolution and repair in atherosclerotic plaques ( 87 ).…”
Section: Pathogenesismentioning
confidence: 99%